Association of Portal Vein Doppler Parameters with Chronic Liver Disease Child Pugh Classes: A Single Center Experience at Rawalpindi, Pakistan - Abdul Ahad Farooq , Ahsen Farooq , Muhammad Rashid , Junaid Haris Farooq , Salma Umbreen , Rabia Waseem (Journal of Islamic International Medical College, 2019)
Objective: To determine the association between Doppler Parameters of average peak portal vein velocity and flow direction and Child Pugh classes of patients suffering from the chronic liver disease. Study Design: It was a descriptive study. Place and Duration of Study: The study was conducted from December 2013 to January 2015 at the Radiology Department of Holy Family Hospital, Rawalpindi, Pakistan. Materials and Methods: Selected chronic liver disease (CLD) patients were examined with gray scale and Doppler USG for assessment of portal vein (PV). Average peak portal venous velocity (PVV) and direction of flow in the main portal vein were recorded. Doppler findings were correlated with clinical features and laboratory findings in three classes (A,B & C) of patients using Child Pugh criteria to establish any probable association between them (appendix: I). Results: Out of total 115 CLD patients studied, 47.8% were in Child Pugh class C. The main portal vein average PVV (cm/sec) in 24.34% patients with Child Pugh class A was 18.75 + 1.88, in 27.82% patients with Child Pugh class B was 14.25 + 0.98 and in 47.82% patients with Child Pugh class C was 8.15 + 1.84. This showed significant fall in portal vein average PVV with advancing Child Pugh class of cirrhosis. Only 10.4% patients showed continuous hepatofugal flow and 4.3% showed bidirectional flow. It was recorded only in Child Pugh class Cpatients. Conclusion: Doppler findings of average peak velocity in the main portal vein fall progressively with worsening of the Child Pugh class. In addition, the direction of flow is also reversed in cases of the Child Pugh class C cirrhosis.